Evaluation of a pain curriculum for occupational therapists: experiences from a master's-level graduate program over six years. (October 2013) - Rochman, Deborah L.; Sheehan, Michael J.; Kulich, Ronald J.
Abstract Purpose: Deficiencies in pain knowledge and attitudes among students and health practitioners are well documented. Occupational therapists (OTs) commonly care for patients who present with pain, and their knowledge of the field presumably impacts that care. This study presents the results of testing OT students' pain knowledge in order to assess the effects of embedding pain teaching in a generic master's-level OT course and to determine specific topics that should be addressed to improve upon existing OT curricula. Method: During the academic years 2004 through 2009, 194 OT students were administered a test of pain knowledge and attitudes on the first and last day of a required class which focused on procedural reasoning. Results: The results indicated significant (p < 0.001) improvement in test scores after participation in the class. Whereas only 35% of students met the minimum "adequate" standard for pain knowledge at pre-test, 92% of students met this standard at post-test. Conclusions: The results demonstrate the effectiveness of a course taught by an instructor with pain expertise. In addition, analysis of individual items highlights the need for curricula to address theoretical versus practical understanding of pain, the ever-evolving science of pain, and pervasive biases about specific pain topics. Implications for Rehabilitation Deficiencies in pain knowledge and attitudes among students and health practitioners are well documented. Occupational therapists (OTs) commonly care for patients who present with pain, and their knowledge of the field presumably impacts that care. The results of this study demonstrate the effectiveness of an OT course taught by an instructor with pain expertise. OT curricula should address pain in special populations (e.g. children and the elderly), acute versus chronic pain, theoretical versus practical understanding of pain, the ever-evolving science of pain, and pervasive biases about specific pain topics (e.g. malingering and opioid addiction).